Proceedings of the 10th ACM Symposium on Information, Computer and Communications Security 2015
DOI: 10.1145/2714576.2714636
|View full text |Cite
|
Sign up to set email alerts
|

Access Control in Publicly Verifiable Outsourced Computation

Abstract: Publicly Verifiable Outsourced Computation (PVC) allows devices with restricted resources to delegate expensive computations to more powerful external servers, and to verify the correctness of results. Whilst highlybeneficial in many situations, this increases the visibility and availability of potentially sensitive data, so we may wish to limit the sets of entities that can view input data and results. Additionally, it is highly unlikely that all users have identical and uncontrolled access to all functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…For functions with more than one output bit, the client has to repeatedly (for each output bit) launch several instances of the protocol. Alderman et al [1,2] also propose an ABE-based protocol for Boolean functions. The authors adopt a scenario orthogonal to ours, in which queriers are identified according to access control policies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For functions with more than one output bit, the client has to repeatedly (for each output bit) launch several instances of the protocol. Alderman et al [1,2] also propose an ABE-based protocol for Boolean functions. The authors adopt a scenario orthogonal to ours, in which queriers are identified according to access control policies.…”
Section: Related Workmentioning
confidence: 99%
“…The authors adopt a scenario orthogonal to ours, in which queriers are identified according to access control policies. Furthermore, Alderman et al [1,2] introduce the concept of blind verifiability. In a nutshell, their protocols distinguish queriers from verifiers: The latter may only be authorized to verify an outsourced computation but not to learn its results.…”
Section: Related Workmentioning
confidence: 99%
“…For the public delegation and the public verifiable property, Applebaum et al 's works did not satisfy them, as well as the work presented in [13,14,19]. Reference [11] presented SV-OC protocol supported Type I computation outsourcing but neglected Type II one, so was the hybrid [20,21] notion for verifiable computation failing the scalable property. We note that all approaches to construct VC protocols except for functional encryption-based method failed to provide public delegation property for a verifiable outsourcing protocol towards a group of clients.…”
Section: Related Workmentioning
confidence: 99%
“…Key distribution center also issues the certificates to the honest server to whom a delegator may outsource the computation. Recently, the authors put forward some extension based on this approach in the sense of access control [94] and hybrid protocol [95].…”
Section: Fully Homomorphic Encryption (Fhe)mentioning
confidence: 99%